After Ripening in Juniperus macropqda - Dabral, S. N. (Indian Forester, 1948)
Junipcrus macropoda Seeds ordinarily do not give more than 1 per cent germination, The dormancy is due to after-ripening required: 2 years old seed co1luted in December and stored under ground for 2-3 months has given upto 20 per cent germination, Treated seeds enter Into a secon 1ary dormancy after about 30 days of sowi